DEVELOPMENT STRATEGY IN CIREBON USING TAWHIDI METHODOLOGY STRING RELATION - Siti Komara (Proceedings of the 1st International Conference on Social Science (ICSS), 2022)
Development about amount traveler Muslims who continue increase be one _ potency big for could interesting interest they visit to a particular region or country . Policies that govern about Halal tourism is also made by the Government , one of which is is indicator halal tourism that requires existence religious symbols in travel . Study this aim for see halal travel with perspective different , no only use indicator halal tourism that has been formulated by the government but also with use methodology Tawhidi String Relations, a method view that uses aspect interaction , integration and evolution for realize sustainability and well- being for the actors involved in halal tourism . So that "halal" is not only Becomes a jargon but be "the way of life". Method research used _ is descriptive qualitative with source data comes from results interviews , observations and literature review . Research location performed on several object tourism in the city of Cirebon with the actors involved in Halal tourism including manager object tourism , MSMEs around object tourism and government area Cirebon Regency . Research results showing interaction , integration and evolution occur Among manager object tourism and society so that productivity object tour increase every year seen from amount visit tourists and turnover _ _ as well as absorption power work whereas Among government area with managers and SMEs yet there is a process of interaction , integration and evolution.